Internet resource as a tool of university public relations in the competitive environment of educational services. (Herald of Journalism, 2016)
This article aims to explore the subject of Public Relations and the Internet, provide an analysis of the university websites and recommendations on improving Public Relations by means of new communication technologies in the Internet.
Keywords: Internet; Web; Internet Public Relations; Higher Education PR.